2022
DOI: 10.3390/su142315620
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Design of K-12 Artificial Intelligence Education: A Systematic Review

Abstract: In response to the growing popularity of artificial intelligence (AI) usage in daily life, AI education is increasingly being provided at the K-12 level, with relevant initiatives being launched worldwide. Examining how these programs have been implemented and summarizing useful experiences is thus imperative. Although prior reviews have described the characteristics of AI education programs in publications, the papers reviewed were mostly nonempirical reports, and the analysis typically only involved a descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…In a scoping review, Su et al (2023) have identified various teaching methods in AI classrooms, such as inquiry-based learning, project-based learning, and game-based learning. In another review by Yue et al (2022), direct instruction has remained a most popular pedagogy in delivering AI concepts, whereas hands-on, experiential activities are often incorporated to enhance student engagement. From the literature review, while most of current pedagogical approaches involves applying established pedagogical framework in AI classrooms, there appears to be a limited focus on the development of domain-specific pedagogy tailored for upper primary students.…”
Section: Using Humans As a Reference To Teach Artificial Intelligencementioning
confidence: 99%
“…In a scoping review, Su et al (2023) have identified various teaching methods in AI classrooms, such as inquiry-based learning, project-based learning, and game-based learning. In another review by Yue et al (2022), direct instruction has remained a most popular pedagogy in delivering AI concepts, whereas hands-on, experiential activities are often incorporated to enhance student engagement. From the literature review, while most of current pedagogical approaches involves applying established pedagogical framework in AI classrooms, there appears to be a limited focus on the development of domain-specific pedagogy tailored for upper primary students.…”
Section: Using Humans As a Reference To Teach Artificial Intelligencementioning
confidence: 99%
“…The acquisition of knowledge in AI represents a great pedagogical challenge for both experts and teachers, and a cognitive challenge for students (Micheuz, 2020). Some countries are making significant efforts to promote AI education in K-12 (Touretzky et al, 2019b), by developing relatively comprehensive curriculum guidelines (Yue et al, 2021). Through interviews with practitioners and policy makers from three different continents (America, Asia and Europe), some studies report on continuing works to introduce AI in K-12 education (He et al, 2020).…”
Section: Integration Of Ai Into the K12 Curriculummentioning
confidence: 99%
“…Through interviews with practitioners and policy makers from three different continents (America, Asia and Europe), some studies report on continuing works to introduce AI in K-12 education (He et al, 2020). Some other work focuses on examining and comparing AI curricula in several countries (Yue et al, 2021). In addition, there are a growing number of AI training experiences that explore pathways to optimize AI learning for K-12 students.…”
Section: Integration Of Ai Into the K12 Curriculummentioning
confidence: 99%
See 2 more Smart Citations